2007
DOI: 10.1089/oli.2006.0062
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Two Cationic Delivery Systems for siRNA

Abstract: Small interference RNA (siRNA) is an important research tool, and also has the potential for clinical application. RNA interference (RNAi) approaches allow degradation of selective mRNA coding for pathogenic or disease-related proteins. RNAi pathway can be taken advantage of by the delivery of chemically synthesized siRNA. To fully attain its potential a sufficient siRNA must be delivered to the cell's cytoplasm. Cellular delivery of polyanions such as siRNA, while a challenging problem, may be addressed by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 51 publications
(48 reference statements)
0
14
0
Order By: Relevance
“…In the case of Lipofectamine, no siRNA could be released from the lipoplexes with heparin. However, recent studies showed that lipoplexes decomplex more easily than polyplexes, which can be explained by their fusogenic properties with cell membranes leading to the release of the siRNA [39].…”
Section: Heparin Competition Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of Lipofectamine, no siRNA could be released from the lipoplexes with heparin. However, recent studies showed that lipoplexes decomplex more easily than polyplexes, which can be explained by their fusogenic properties with cell membranes leading to the release of the siRNA [39].…”
Section: Heparin Competition Assaymentioning
confidence: 99%
“…As mentioned above biodegradability is a key factor for long-term pulmonary application to avoid side-effects caused by accumulation [39][40][41]. The first breakthrough in pulmonary drug delivery was achieved with PLGA microparticles [42], due to their low toxicity and biodegradable character.…”
Section: Heparin Competition Assaymentioning
confidence: 99%
“…The intracellular delivery efficiency of cationic lipid-based nanoparticles can be affected by the type of cationic lipids used (Akinc et al, 2008), meaning that the selection of cationic lipids is critical for effective internalization of siRNA in magnetic lipoplexes. Moreover, as compared with polyplexes, lipoplexes were reported to decomplex more easily in the cells (Yadava et al, 2007). Since glutamic acid-derived cationic lipid DG was previously shown to help boost intracellular delivery of siRNA after 24 hours of incubation (Suh et al, 2009), we herein tested the magnetofection of DG-based cationic liposomes.…”
Section: Discussionmentioning
confidence: 99%
“…Significant efforts have been placed, therefore, on developing nanoparticle technologies to facilitate siRNA cellular uptake. A wide range of molecules have been developed as delivery systems, and they include cationic lipids, carbon nanotubes, poly(lactic-coglycolic) acid (PLGA), polyethylenimine (PEI), peptides, dendrimers, and silicon and gold microparticles [5-11]. PEI has been used as an effective DNA plasmid delivery vehicle but has limited capacity for siRNA delivery [5,12].…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of molecules have been developed as delivery systems, and they include cationic lipids, carbon nanotubes, poly(lactic-coglycolic) acid (PLGA), polyethylenimine (PEI), peptides, dendrimers, and silicon and gold microparticles [5-11]. PEI has been used as an effective DNA plasmid delivery vehicle but has limited capacity for siRNA delivery [5,12]. Recently, Bolcato-Bellemin and colleagues extended the 3' end of the siRNA creating longer complimentary overhangs of five or eight nucleotides, thereby allowing PEI to effectively deliver these siRNA molecules into cells [13].…”
Section: Introductionmentioning
confidence: 99%